Linguoconcentual Nature of Intellectual Parameters in Kazakh Legal Discourse - Bakytzhanova, Altyn; Zhanzhigitov, Syrym; Bibekov, Kanysh; Yelubay, Assem; Mussabayeva, Aliya (Forum for Linguistic Studies, 2025)
The relevance of the scientific article is conditioned by the need for a comprehensive understanding of the cognitive nature of legal discourse in the conditions of transformation of the Kazakh legal system and strengthening the role of language in legal regulation. The study is aimed at identifying and systematising the linguoconceptual features of such intellectual parameters as ‘kukyk’, ‘korgau’, ‘qorlau’, “adildik”, ‘tendik’, etc., which play a key role in the formation of legal norms, concepts and legal reasoning. Theoretical significance of the study lies in the expansion of the conceptual apparatus of linguoconceptology of law and clarification of cognitive-discursive models used in Kazakh legal language. The practical value of the study is manifested in the possibility of applying the results obtained in legal translation, legal education, examination of normative texts and forensic linguistics. This study offers a focused analysis of the semantic and intellectual dimensions of Kazakh legal discourse—an area that remains underexplored in current legal linguistic research. By highlighting how native speakers interpret legal concepts, the research helps bridge the gap between national legal language practices and international legal communication standards. It contributes to existing scholarship by offering insights that can enhance legal translation, support the development of linguo-legal frameworks, and inform policy-making in the digital age. Ultimately, this work lays essential groundwork for future interdisciplinary studies at the crossroads of linguistics, law, and cognitive science, promoting both the preservation and modernization of Kazakh legal language.